Forced deportations and the Ukraine war: Russian culpability in atrocity crimes. Issue 2 (October 2022) - Colvin, Victoria; Orchard, Phil
Since the war in Ukraine has begun, Russia has used population transfers as one of its tactics of war with over 3.6 million Ukrainian citizens now in Russia. These are acts that both Ukrainian authorities and other governments including the United States have claimed are forced deportations. This pattern reflects a longer history—the Soviet Union frequently used similar population transfers as forms of collective punishment against potentially rebellious populations, and the Russian government used similar tactics in both Chechnya and Syria. But in this case, we have better evidence of these movements as they occur. Forced deportations and transfers are defined both as war crimes—under the Fourth Geneva Convention and Additional Protocol II and Article 8 of the Rome Statute—and as crimes against humanity—under Article 7 of the Rome Statute. Therefore, as forced deportations constitute both war crimes and crimes against humanity, there are a number of mechanisms by which individual Russian perpetrators of these acts can be held accountable. These include, with the Ukrainian government's acceptance of its jurisdiction, the International Criminal Court. But such accountability mechanisms also exist at the individual state level through universal jurisdiction and Magnitsky sanctions legislation.